2017
DOI: 10.1097/md.0000000000005817
|View full text |Cite
|
Sign up to set email alerts
|

Expression quantitative trait loci for PI3K/AKT pathway

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Moreover, COL4A1 mutations resulted in an excess of the apoptosis of endothelial cells contributing to primary endothelial cell defects and COL4A1 ‐related myopathy in mice . In 2016 it was shown that upregulated COL4A1 had all homozygotes of minor alleles at single nucleotide variants in lymphoblastoid cell lines . Because COL4A1 synthesizes a major complex of plasma membrane and activates fibroblasts through the PI3K/AKT pathway, it might be a candidate gene for predicting patients’ genetic susceptibility to cancer and could be used in targeted cancer therapy .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, COL4A1 mutations resulted in an excess of the apoptosis of endothelial cells contributing to primary endothelial cell defects and COL4A1 ‐related myopathy in mice . In 2016 it was shown that upregulated COL4A1 had all homozygotes of minor alleles at single nucleotide variants in lymphoblastoid cell lines . Because COL4A1 synthesizes a major complex of plasma membrane and activates fibroblasts through the PI3K/AKT pathway, it might be a candidate gene for predicting patients’ genetic susceptibility to cancer and could be used in targeted cancer therapy .…”
Section: Discussionmentioning
confidence: 99%
“…31 Because COL4A1 synthesizes a major complex of plasma membrane and activates fibroblasts through the PI3K/AKT pathway, it might be a candidate gene for predicting patients' genetic susceptibility to cancer and could be used in targeted cancer therapy. 31 However, a correlation F I G U R E 4 Identification of candidate genes associated with prognosis. A, Kaplan-Meier plot indicates that increased collagen type IV alpha 1 (COL4A1) expression had a poorer prognosis (P = 0.04).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our pathway figure OCR results, there were over 600 figures with more than 100 genes each. While many of the largest figures are interaction networks, the largest with 385 recognized genes is an augmented KEGG pathway where the authors properly listed the individual gene family and paralog members referenced generically in the original [ 29 ]. At the other end, there was a long tail of just over 20k (37%) figures that had fewer than seven recognized genes.…”
Section: Contentmentioning
confidence: 99%
“…In our pathway figure OCR results, there were over 600 figures with more than 100 genes each. While many of the largest figures are interaction networks, the largest with 385 recognized genes is an augmented KEGG pathway where the authors properly listed the individual gene family and paralog members referenced generically in the original 26 . At the other end, there was a long tail of just over 20k (37%) figures that had fewer than seven recognized genes.…”
Section: Genes In Pathway Figuresmentioning
confidence: 99%